Analysis of Customer Needs in the House of Quality to Improve the Quality of Inpatient Room Services at Hospital X in Yogyakarta - Wati, Erlin Susilo; Hasuti, Siti Kurnia Widi; Rokhmayanti, Rokhmayanti; Astuti, Fardhiasih Dwi; Selly Aprianda Syah Putri (Universitas Ahmad Dahlan, 2024)
Background: House of Quality is a matrix that is widely used to achieve higher customer satisfaction. Hospital X in Yogyakarta City is one of the Private Hospitals type B, The number of unstable patient visits each year and the presence of various patient complaints may be caused by several factors that influence patient perceptions in choosing health services in inpatient installations. The purpose of this study was to analyze Customer Need in the House of Quality (HOQ) in improving the quality of service in the Inpatient Installation of Hospital X in Yogyakarta City. Methods: This study uses a qualitative method with a phenomenology design type. The method of selecting subjects uses a purposive sampling method with the consideration of researchers, namely, patients from the VIP sakinah ward of Hospital X in Yogyakarta City with details, 3 key informants with a minimum of 2 days of care. While the triangulation informants are 3 people. with details, 1 Ward Officer, 1 Service Quality Committee Officer, 1 Public Relations and Marketing Officer. Results: Based on the results of the analysis of 5 dimensions, tangibles, reliability, responsiveness, assurance and empathy. Each patient gives their own perception and expectations, there is one dimension of service quality that patients consider less good, namely the empathy dimension. In the empathy dimension, patients feel that officers have not fully paid attention to patients. Conclusion: there is one dimension of service quality that patients consider less good, namely the empathy dimension, as a quality improvement strategy, hospitals can conduct excellent service training.